An annotated and illustrated catalogue of the Osmylidae collection (Neuroptera) at the Natural History Museum, London - Martins, Caleb Califre; Price, Benjamin W. (Zootaxa, 2020)
The Natural History Museum, London, houses of one of the largest insect collections in the world including several hundred specimens of the small lacewing family Osmylidae. Herein we provide the complete label information, specimen condition, locality and habitus pictures of the Osmylidae primary types of the Natural History Museum, with some historical information about the specimens.